Environmental Pollution Module Based on SETS with Islamic Value to Improve Student' Science Literacy - Nisa, Khaerun; Indriyanti, Dyah Rini; Parmin, Parmin (Universitas Negeri Semarang, 2022)
This study aims to test the feasibility and effectiveness of the SETS-based environmental pollution module with Islamic values ​​in improving students' scientific literacy. This type of research is research and development (R&D) that uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects to test the developed module were 39 students and three expert lecturers consisting of science material experts, Islamic religious material experts, and media experts. The research instruments were expert validation questionnaires, legibility questionnaires, gaps test questions, and scientific literacy test questions. The expert validation data analysis showed the average score on the feasibility aspects, which were considered very valid. The readability questionnaire analysis describes the module as having excellent readability. This result is in line with the results of the gap test analysis that the module is easy for students to understand. The N-gain values ​​for the three aspects of scientific literacy are 0.46, 0.45, and 0.38 in the medium category, while the other element is 0.26 in the low class. Based on the analysis results, the environmental pollution module SETS-based with Islamic values ​​was very suitable for learning. It was effective in improving three aspects of scientific literacy.